Understanding the concept of density through investigative teaching and representations - Botelho, Maria Luiza Silva Tupy; Quadros, Ana Luiza de; Fernandes, Giovana França Carneiro; Dias, Mariana Gonçalves (Seven Editora, 2023)
Associating teaching assumptions through investigations with the role of representations has been promising in terms of learning. We developed this work with students of the first year of High School with the objective of analyzing the contributions of science teaching by investigation in the involvement of students with the problem issue and with the use of representations as tools that facilitate conceptual understanding. The students were challenged to propose an experiment that would help them solve the problem and to communicate in pairs the path taken and the explanation for the phenomenon present in the experiment. We observed that the students were actively involved in explaining the phenomenon and, for that, they appropriated representations that helped both in organizing their own ideas and in communicating with peers. DOI:https://doi.org/10.56238/uniknowindevolp-148